2020
DOI: 10.1016/j.devcel.2020.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Lamin B2 Levels Regulate Polyploidization of Cardiomyocyte Nuclei and Myocardial Regeneration

Abstract: Highlights d Lamin B2 regulates nuclear envelope breakdown and M-phase progression d Decreased Lamin B2 levels lead to formation of polyploid nuclei d Increased prevalence of polyploid nuclei decreases myocardial regeneration in mice d Modifying LMNB2 expression in human cardiomyocytes alters ploidy of nuclei

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 53 publications
4
63
0
Order By: Relevance
“…Our results show that STAT3 is not be activated in Mydgf-treated CMs, indicating that STAT3 signaling is not involved in Mydgf-indcued CM proliferation. We also found that Mydgf deficiency reduced karyokinesis, and thereby increased ploidy, which is coincided with reported data 17 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results show that STAT3 is not be activated in Mydgf-treated CMs, indicating that STAT3 signaling is not involved in Mydgf-indcued CM proliferation. We also found that Mydgf deficiency reduced karyokinesis, and thereby increased ploidy, which is coincided with reported data 17 .…”
Section: Discussionsupporting
confidence: 92%
“…Unlike adult, neonatal mammalian heart is able to regenerate after various types of injury 8 , but this regenerative process seems to be limited to the first postnatal week 9 , 10 , which coincides with CM exiting from the cell cycle 11 - 13 , CM cell-cycle withdrawal during mammalian postnatal development is tightly coupled with CM polyploidization, an increase in nuclear DNA content 14 . It has been demonstrated that troponin I3 kinase levels 15 or insulin-like growth factor 1 16 could change the percentage of polyploid CM nuclei, which altered heart regeneration 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of mechanisms, Kaplan-Meier plots for LMNB1 -scaling genes in primary lung tumors include LMNB2, BRCA1, MKI67 , and TOP2A ( Fig.S3a, S4a,b,c ), all of which show poor survival for high expression ( Fig.S4d,e ). Recent studies of proliferating, embryonic cardiomyocytes suggest LMNB2 facilitates attachment of microtubules to centromeres 42 . Such survival predictions are perhaps consistent with LMNB1 -scaling in tumor but not normal liver tissue (per Fig.2b ) and with LMNB1 being a marker of proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Page 7 of 30 attachment of microtubules to centromeres 42 . Such survival predictions are perhaps consistent with LMNB1-scaling in tumor but not normal liver tissue (per Fig.2b) and with LMNB1 being a marker of proliferation.…”
Section: Gene-gene Scalingmentioning
confidence: 99%
“…Nuclear lamina filament Lamin B2 (Lmnb2) expression decreases after birth coinciding with the closure of the neonatal regenerative window in mice. It enables metaphase progression and its suppression increased CM polyploidization and reduced cardiac regeneration in neonatal mice (Han et al 2020 ).…”
Section: New Players: Cellular Participators and Molecular Regulatorsmentioning
confidence: 99%